PENERAPAN POLA MAKAN SEHAT (B2SA) UNTUK MENURUNKAN ANGKA STUNTING PADA ANAK USIA 2-5 TAHUN DI LINGKUNGAN X KELURAHAN LALANG KECAMATAN MEDAN SUNGGAL - Widya, Rika; Salma Rozana; Cholidah, Cholidah (Bajang Institute, 2025)
Stunting in early childhood is a profound health problem that affects children's physical and cognitive development and health status. This study aims to identify the factors causing stunting in children aged 2-5 years in Neighborhood X, Lalang Village, Medan Sunggal District and to test the effectiveness of the Diverse, Nutritious, Balanced, and Safe (B2SA) healthy diet approach in reducing the prevalence of stunting. This study used a qualitative approach with data collected through observation, interviews, and documentation. The results showed that the main factors causing stunting were insufficient nutritional intake, low socioeconomic status, and parents' lack of understanding about balanced nutrition. Efforts to reduce stunting were made by educating parents about the importance of B2SA and providing healthy food assistance tailored to children's needs.